The Effect of Service Quality on Credit Life Insurance Customer Satisfaction - Reinardo Simon Louhenapessy; Hastuti Naibaho (Amkop Management Accounting Review (AMAR), 2026)
The insurance industry in Indonesia has experienced steady growth; however, its insurance penetration rate remains relatively low compared with other Southeast Asian countries. Credit Life Insurance plays an important role in mitigating credit risk for financial institutions while providing financial protection for borrowers. In this context, service quality becomes a key determinant of customer satisfaction. This study aims to examine the effect of service quality on customer satisfaction in Credit Life Insurance using the Service Performance (SERVPERF) model within the Stimulus–Response theoretical framework. A quantitative explanatory design was employed with 159 insured in the Greater Jakarta area selected through purposive sampling. Data were collected through an online questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that service quality explains 68.5% of the variance in customer satisfaction. Technology and Personalized Financial Planning show the strongest influence, while other dimensions—Assurance, Competence, Tangibles, and Corporate Image—demonstrate positive but relatively smaller effects. These findings highlight the growing importance of digital service capability and personalized financial services in shaping customer satisfaction in the modern insurance industry. The study contributes to extending SERVPERF application in the Indonesian life insurance context.